The Millennial Generation Special Education Teacher: Promise or Problem - Mehrenberg, Rich (Journal of the American Academy of Special Education Professionals, 2011)
Young Americans born between 1982 and 2002 (also known as members of the Millennial Generation) are now or soon will be beginning their careers in many professions, including special education. This article describes why Millennial Generation special education teachers are vital to the current and future development of the field. It also details commonly reported traits of these individuals that may have a positive or negative impact on their efforts to educate children with exceptionalities. Specific strategies for teacher educators, special education supervisors, co-workers, and other stakeholders are discussed as to how to best guide and support these teachers.